Uji Daya Hambat Ekstrak Lidah Buaya (Aloe barbadensis miller) terhadap Pertumbuhan Bakteri Propionibacterium Acnes - Asyahra, St. Fatima; Islawati, Islawati; Arwie, Dzikra (Journal of Multidiscipline and Collaboration Research, 2024)
Aloe vera (Aloe barbadensis miller) contains antibacterial compounds such as tannins and saponins, which have the potential to combat Propionibacterium acnes, the bacteria responsible for acne. This study aims to evaluate the inhibitory effect of aloe vera extract on P. acnes through a laboratory experimental method. The extract was obtained through maceration using various concentrations: 20%, 40%, 60%, 80%, and 100%. Testing was conducted in triplicate, with clindamycin as the positive control and distilled water as the negative control. The well diffusion method was used for testing, followed by analysis with a One-Way ANOVA test. Results showed p = 0.000, indicating that aloe vera extract significantly inhibits P. acnes. Post hoc LSD analysis revealed significant differences between concentrations, except between clindamycin and the 100% concentration (p > 0.05). The highest mean inhibition zone was found at the 100% concentration (16.6 mm) and the lowest at 20% (9.3 mm). This study suggests that aloe vera extract has potential as a natural antibacterial agent for acne treatment, providing an alternative to reduce synthetic antibiotic use and the risk of bacterial resistance.